Implementasi Self-Management Hidrasi dalam Pembelajaran PJOK: Dampaknya terhadap Stabilitas Fisik dan Kelelahan - Devid Ilhamna; Muchammad Ishak; Bangbang Syamsudar (Jurnal Porkes, 2026)
This study addresses the problem of low student awareness regarding hydration during Physical Education, Sports, and Health (PJOK) learning, which can lead to decreased physical stability and increased fatigue. The aim was to analyze the effect of implementing hydration self-management on students' physical stability and fatigue levels. A quantitative approach with a quasi-experimental method and pretest-posttest control group design was used. The research involved 69 eighth-grade students from SMPN 2 Tanjungsari, Bogor Regency, consisting of 35 students in the experimental group and 34 in the control group. Data were collected through physical stability tests and fatigue questionnaires, then analyzed using normality tests, homogeneity tests, and Independent Sample t-tests. The results showed that the experimental group's physical stability increased from 68.42 to 82.15, while the control group increased from 69.10 to 73.25. Fatigue levels in the experimental group decreased from 74.30 to 60.12, compared to a decrease from 73.85 to 69.40 in the control group. Hypothesis testing yielded significance values of 0.000 for physical stability and 0.001 for fatigue (p < 0.05). In conclusion, implementing hydration self-management in PJOK learning significantly improves physical stability and reduces student fatigue, with a very large practical effect (Cohen's d > 1.6).